The effects of training type and area size variations on the physiological and session rating of perceived exertion responses during male judo matches - Houcine, Nizar; Ouergui, Ibrahim; Bouassida, Anissa; Franchini, Emerson; Bouhlel, Ezdine (Biology of Sport, 2024)
Modified exercise prescription in judo is commonly used to activate the energy systems in different magnitudes. In order to study the physiological and rating of perceived exertion (RPE) responses according to area sizes (i.e., 4 m×4 m, 6 m×6 m and 8 m×8 m) and training mode variations (i.e., groundwork, ne-waza; standing combat only, tachi-waza; and free combat, free randori), eighteen male judo athletes (age: 22.6±1.8 years) were randomly assigned, on separate days, to 9 experimental conditions (3 area sizes×3 training modes) with each condition lasting 4 min. Delta lactate [La] was calculated based on the blood lactate values measured before and after every condition. Heart rate (HR) was measured during and after each bout and RPE recorded at the end of each combat. The results showed that mean and peak HR, percentage of maximum HR (% HR max ), delta [La] values and RPE scores were lower in 4 m×4 m compared to 6 m×6 m and 8 m×8 m, and in groundwork training mode compared to standing combat and free randori (all p < 0.001). Furthermore, the 6 m×6 m condition induced lower delta [La] values than 8 m×8 m (p < 0.001) and free randori resulted in higher RPE scores than standing combat (p = 0.001). In conclusion, different training variables can be easily manipulated in a variety of different ways to specifically activate the energetic systems. Focusing on groundwork, the 6 m×6 m area size was found to be the most suitable condition to induce a higher cardiovascular response, while the standing combat and free randori in 6 m×6 m resulted in increased glycolytic activation compared to the groundwork condition.